Identifikasi Kerusakan pada Gedung Gereja Suara Kebenaran Injil (GSKI Perdatam) di Perdatam, Jakarta Selatan - James Rilatupa; Sahala Simatupang (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM), Univesitas Kristen Indonesia, 2020)
Abstract The potential for damage to a building, whether old or relatively new, is very large. Generally, the appearance of the damage that occurs is visible after the building starts operating. This community service aims to predict the value of the construction conditions of the GSKI Perdatam building on Jl. Pengadegan Utara Raya No. 29, Pancoran, South Jakarta. In addition, this PKM is also useful for knowing the cause of the damage to the building components, so that it can help the management of the GSKI Perdatam Building in its maintenance aspects. The method used is to identify the type of damage, both in terms of architecture, construction management and maintenance. Damage to the GSKI Perdatam building occurred in the roof, ceiling, walls, floors, utilities and sanitation components. Damage weight ranges from 10 - 75 percent for each of the damaged components. Most of the damage caused by rainwater seepage. The smallest damage was found in the floor components (10 percent) caused by popping; and the largest in the wall component (75 percent). Keywords: damage identification; building components.